2014
DOI: 10.1007/s10549-014-2912-z
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine promotes apoptosis resistance of breast cancer cells and enrichment of side population cells with cancer stem cell-like properties via a signaling cascade involving galectin-3, α9 nicotinic acetylcholine receptor and STAT3

Abstract: Nicotine, a main addictive compound in tobacco smoke, has been linked to promotion and progression of lung, head and neck, pancreatic, and breast cancers, but the detailed mechanisms of cancer progression remain elusive. Here we show that nicotine induces the expression of galectin-3 (an anti-apoptotic β-galactoside-binding lectin) in breast cancer cell line and in primary tumors from breast cancer patients. Nicotine-induced up regulation of galectin-3 is due to an increased expression of α9 isoform of nicotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 60 publications
2
59
0
Order By: Relevance
“…Further, BC cells expressing activated STAT3 exhibit poorer therapeutic response to neo-adjuvant chemotherapy [61], and a role of STAT3 in the maintenance of BC stemness has also been well explored [39, 62]. Guha et al demonstrated a critical role of STAT3 in apoptosis resistance and development and maintenance of CSC characteristics in breast cancer cells [63]. In other cancers, such as pancreatic cancer, STAT3 has been shown to be important in maintaining stem cell phenotypes [32].…”
Section: Discussionmentioning
confidence: 99%
“…Further, BC cells expressing activated STAT3 exhibit poorer therapeutic response to neo-adjuvant chemotherapy [61], and a role of STAT3 in the maintenance of BC stemness has also been well explored [39, 62]. Guha et al demonstrated a critical role of STAT3 in apoptosis resistance and development and maintenance of CSC characteristics in breast cancer cells [63]. In other cancers, such as pancreatic cancer, STAT3 has been shown to be important in maintaining stem cell phenotypes [32].…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, two sets of each cell monolayer were scratched using a pipette tip [29]. One set of each cell was treated with 10 mM Neu5Ac in PBS for 2 h as described above in “Neu5Ac treatment” and after washing, the cells were incubated in the complete medium for additional 24 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Gal-3 has been considered a tumor-associated antigen of malignancy level in breast cancer, and is implicated in aspects, such as angiogenesis [219], adhesion [220], invasion [221], apoptosis inhibition [222], migration [223], and therapeutic resistance [224]. Chen et al, through hydrazide-based chemistry method combined with liquid chromatography tandem-mass spectrometry (LC-MS/MS), identified 72 unique N-linked glycoproteins that were significantly regulated in triple negative breast cancers, among which is LGALS3BP.…”
Section: Hypoxia Alters Cell Location Of Galectins and Interaction Wimentioning
confidence: 99%